2002
DOI: 10.1590/s0102-311x2002000100021
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do processo da atenção médica: adequação do tratamento de pacientes com diabetes mellitus, Pelotas, Rio Grande do Sul, Brasil

Abstract: A study was conducted in 1998 with the aim of assessing adequacy of clinical management of diabetic patients attending public health services in Pelotas, Brazil. Patients were interviewed to gather data on medical consultation, disease, and treatment. Data analysis focused on the "type of treatment" variable with three categories: diet, physical activity, and drug treatment. Seventy-six percent of the patients reported having received nutritional orientation. Only 50% of them reported having followed their die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
29

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 9 publications
(7 reference statements)
0
4
0
29
Order By: Relevance
“…26 We found that adhesion to outpatient care at basic healthcare units -in which the Family Health program is conducted -was significant in both groups. Monthly visits include discussing healthcare measures for diabetes and high blood pressure, although blood glucose levels are not monitored at these units, which lack glucometers.…”
Section: Discussionmentioning
confidence: 70%
“…26 We found that adhesion to outpatient care at basic healthcare units -in which the Family Health program is conducted -was significant in both groups. Monthly visits include discussing healthcare measures for diabetes and high blood pressure, although blood glucose levels are not monitored at these units, which lack glucometers.…”
Section: Discussionmentioning
confidence: 70%
“…Os pontos de corte de glicemia como critério diagnóstico da doença são amplamente discutidos na atualidade, e a classificação rotineiramente empregada é: diabetes tipo 1 (anteriormente denominado insulinodependente), diabetes tipo 2 (não insulinodependente) e diabetes gestacional. Atualmente, a indústria farmacêutica dispõe de numerosas drogas para o tratamento do diabetes, porém o controle metabólico de indivíduos com a doença em evolução consiste em um dos maiores desafios dos serviços de saúde pública (Donahue & Ochard, 1992;Assunção, Santos & Gigante, 2001;Assunção, Santos & Costa, 2002).…”
Section: Considerações Finaisunclassified
“…No entanto, outra biguanidina, a metformina vem sendo utilizada sem apresentar qualquer efeito adverso significativo, diminuindo os riscos de complicações em pacientes com sobrepeso, além de apresentar menos episódios de hipoglicemia, podendo, assim, se transformar em uma droga de primeira escolha no tratamento do DM (ASSUNÇÃO et al, 2002).…”
Section: São Considerados Sintomas Do Dmunclassified